Challenges to the provision of diabetes care in first nations communities: results from a national survey of healthcare providers in Canada - Macaulay Ann C; Toth Ellen; Esler James; Estey Elizabeth A; Naqshbandi Mariam; Rasooly Irit R; Bhattacharyya Onil K; Harris Stewart B (BMC, 2011)
Abstract Background Aboriginal peoples globally, and First Nations peoples in Canada particularly, suffer from high rates of type 2 diabetes and related complications compared with the general population. Research into the unique barriers faced by healthcare providers working in on-reserve First Nations communities is essential for developing effective quality improvement strategies. Methods In Phase I of this two-phased study, semi-structured interviews and focus groups were held with 24 healthcare providers in the Sioux Lookout Zone in north-western Ontario. A follow-up survey was conducted in Phase II as part of a larger project, the Canadian First Nations Diabetes Clinical Management and Epidemiologic (CIRCLE) study. The survey was completed with 244 healthcare providers in 19 First Nations communities in 7 Canadian provinces, representing three isolation levels (isolated, semi-isolated, non-isolated). Interviews, focus groups and survey questions all related to barriers to providing optimal diabetes care in First Nations communities. Results the key factors emerging from interviews and focus group discussions were at the patient, provider, and systemic level. Survey results indicated that, across three isolation levels, healthcare providers' perceived patient factors as having the largest impact on diabetes care. However, physicians and nurses were more likely to rank patient factors as having a large impact on care than community health representatives (CHRs) and physicians were significantly less likely to rank patient-provider communication as having a large impact than CHRs. Conclusions Addressing patient factors was considered the highest impact strategy for improving diabetes care. While this may reflect "patient blaming," it also suggests that self-management strategies may be well-suited for this context. Program planning should focus on training programs for CHRs, who provide a unique link between patients and clinical services. Research incorporating patient perspectives is needed to complete this picture and inform quality improvement initiatives.